Optimalisasi Pemanfaatan Buah Belimbing Wuluh (Averrhoa bilimbi L.) Bagi Ibu-Ibu PKK RT 004 Kelurahan Labuhan Ratu Bandar Lampung - Yulianty; Endang Nurcahyani; Bambang Irawan; Emantis Rosa; Hendri Busman; Salman Farisi; Suratman Umar (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Averrhoa bilimbi L. is a type of plant that grows in yards or home gardens. This species belongs to the order Oxalidales and the family Oxalidaceae. This species belongs to the Oxalidales order and Oxalidaceae family. This plant has many benefits, including its stems, leaves, flowers, and fruit. The women of PKK RT 004 generally use the fresh flowers and fruit. The fresh fruit is used as an addition in making fish pindang as a substitute for tamarind and candis acid. However, the women of PKK have never used preserved fruit as sweets and asam sunti.  Therefore, it is necessary to optimize the use of fruit  by preserving it, such asam sunti.  Asam sunti is commonly used by the people of Aceh. Asam sunti is made from dried fruit, which is salted and dried in the sun repeatedly until the  fruit is dry and brown in color. The results of this community service activity showed good pre-test and post-test scores. The average pre-test score was 92.87 and the average post-test score was 98. There was an increase of 5.33 points. The sustainability of this community service activity is that the PKK mothers of RT 004 can disseminate the information obtained from this activity to other communities.